Non-Cell-Autonomous Factors Implicated in Parvalbumin Interneuron Maturation and Critical Periods - Gibel-Russo, Rachel; Benacom, David; Di Nardo, Ariel A. (Frontiers in Neural Circuits, 2022)
From birth to adolescence, the brain adapts to its environmental stimuli through structural and functional remodeling of neural circuits during critical periods of heightened plasticity. They occur across modalities for proper sensory, motor, linguistic, and cognitive development. If they are disrupted by early-life adverse experience or genetic deficiencies, lasting consequences include behavioral changes, physiological and cognitive deficits, or psychiatric illness. Critical period timing is orchestrated not only by appropriate neural activity, but also by a multitude of signals that participate in the maturation of fast-spiking parvalbumin interneurons and the consolidation of neural circuits. In this review, we describe the various signaling factors that initiate critical period onset, such as BDNF, SPARCL1, or OTX2, which originate either from local neurons or glial cells or from extracortical sources such as the choroid plexus. Critical period closure is established by signals that modulate extracellular matrix and myelination, while timing and plasticity can also be influenced by circadian rhythms and by hormones and corticosteroids that affect brain oxidative stress levels or immune response. Molecular outcomes include lasting epigenetic changes which themselves can be considered signals that shape downstream cross-modal critical periods. Comprehensive knowledge of how these signals and signaling factors interplay to influence neural mechanisms will help provide an inclusive perspective on the effects of early adversity and developmental defects that permanently change perception and behavior.